Case series: Point-of-Care Ultrasound Conducted by Medical Students During their First Clinical Rotation Changes Patients’ Primary Diagnosis and Management - Sadeh, Re'em; Gat, Tomer; Kaplan, Omer; Porges, Tzvika; Zeller, Lior; Barski, Leonid; Fuchs, Lior (International Journal of Medical Students, 2021)
Background: As point-of-care ultrasound (POCUS) becomes a standard of care procedure, medical schools around the world have started to seek the integration of POCUS courses into their curricula. This puts medical students in a unique position as they are trained in an area in which many physicians lack knowledge. This case series provides a glimpse into the capabilities of POCUS even when used by medical students. Methods: Fourth-year medical students at Ben-Gurion University of the Negev performed numerous POCUS exams during their first clinical rotation at Soroka University Medical Center in Israel. All students completed a course in basic POCUS training and were evaluated in a brief practical exam before entering their first clinical rotation. Four of the cases in which the students took part are presented in this case series. Results: The POCUS exam in the first case discovered pulmonary embolism in addition to the diagnosis of Cushing disease. In the second case, endocarditis could have been diagnosed three days earlier had a POCUS exam been performed. Case 3 demonstrates the additional contribution of POCUS to the decision-making process carried out by physicians and its superiority in quantifying and diagnosing pleural effusion compared to chest X-Ray. Case 4 indicated that POCUS is preferable over chest X-ray and auscultation for the diagnosis of pulmonary edema. Conclusion: This case series may emphasize the capabilities POCUS has when utilized in the standard physical examination and the importance of incorporating POCUS instruction in medical schools for new physicians to acquire this skill.